Anatomical Features of Congenital Diaphragmatic Hernia in Children of Different Age - O.K. Slepov; V.L. Veselsky; Ye.O. Slepov; O.P. Ponomarenko; V.P. Soroka; O.P. Dzham; G.S. Yermolova (Zaslavsky O.Yu., 2013)
The article deals with congenital diaphragmatic hernia, which is rare in infants and older children. The analysis of the anatomical features of this malformation has been carried out for 76 operated children aged from 1 month to 15 years. The prevalence of this defect in children of different age groups is determined. We identified anatomical and morphometric features of hernial orifice and nature of the hernial content, depending on the type of congenital diaphragmatic hernia.